Consumer Credit in Europe Risks and Opportunities of a Dynamic Industry - Vandone, Daniela. (Contributions to Economics, 2009)
Consumer credit has become a topical issue for researchers, regulators and the banking industry in Europe as a result of increasing market integration, regulatory changes and a growing tendency of households to use debt to finance consumption. This study uses a cross-country approach to look at a broad range of issues related to consumer credit in Europe. Focusing on both the supply and demand sides, it takes into account the structure and performance of financial intermediaries, the socio-demographic and economic profile of households and their risk of over-indebtedness, as well as the regulatory framework, such as the new Consumer Credit Directive. In the light of this analysis, measures for the prevention and management of over-indebtedness are presented. This book is essential for postgraduate students and specialists in financial institutions, for regulators and policy-makers who are in charge of efficiency and stability of financial systems.